2008
DOI: 10.1177/0192623307313010
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol-induced Cardiotoxicity in Sprague-Dawley Rats: Correlation of Reversible and Irreversible Myocardial Injury with Release of Cardiac Troponin T and Roles of iNOS in Myocardial Injury

Abstract: The present study was undertaken to characterize myocardial lesions in the rat induced by low doses of isoproterenol (Iso) and to correlate lesion severity with release of cardiac troponin T (cTnT) and changes in myocyte iNOS expression. Two types of cardiac injury patterns were observed. A Type I response, noted 3 or 6 hours postdosing with 8, 16, 32, or 64 mug/kg Iso, included potential reversible myocardial alterations associated with slight increases in serum cTnT (< 0.3 ng/mL) and a slight reduction in my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 25 publications
9
72
0
Order By: Relevance
“…The level of mRNA for vascular endothelial growth factor and iNOS are increased in hypertrophied heart induced by abdominal aortic banding (Ji et al, 2008). Administration of isoproterenol increases iNOS immunoreactivity in the heart of Sprague Dawley rats (Zhang et al, 2008). Consistent with these previous results, the present study showed that chronic infusion of isoporterenol increased the protein level of iNOS in the left ventricle.…”
Section: Discussionsupporting
confidence: 93%
“…The level of mRNA for vascular endothelial growth factor and iNOS are increased in hypertrophied heart induced by abdominal aortic banding (Ji et al, 2008). Administration of isoproterenol increases iNOS immunoreactivity in the heart of Sprague Dawley rats (Zhang et al, 2008). Consistent with these previous results, the present study showed that chronic infusion of isoporterenol increased the protein level of iNOS in the left ventricle.…”
Section: Discussionsupporting
confidence: 93%
“…First, serum cTnT and cTnI concentrations return to baseline levels faster, often within 24 h, after diffuse infarctions that occur in the presence of unrestricted blood flow such as after an isoproterenol injection (22)(23)(24). After isoproterenol-induced AMI in rats, necrotic myocytes are diffusely distributed in the heart and exposed to an unrestricted plasma flow, resulting in fast extraction and clearance of cTnT and cTnI, compared with a classical thrombotic AMI when the damage is focal and there is only a limited plasma flow.…”
Section: Discussionmentioning
confidence: 99%
“…Interspersed with this presentation of coagulation necrosis and cardiomyocyte vacuolization, evidence of catecholamine toxicity seen as hypercontraction band necrosis, was also noted. 51 As the duration of time since original seizure induction progressed, the distribution of myocardial necrosis became more extensive around the subendocardial region. By day 14, cardiac tissue morphology was characterized by dead phagocytosed tissue and dense interstitial and perivascular connective tissue.…”
Section: Discussionmentioning
confidence: 99%